2020
DOI: 10.1017/s014271642000017x
|View full text |Cite
|
Sign up to set email alerts
|

How language environment, age, and cognitive capacity support the bilingual development of Syrian refugee children recently arrived in Canada

Abstract: Research on the bilingual development of refugee children is limited, despite this group having distinct characteristics and migration experiences that could impact language development. This study examined the role of language environment factors, alongside age and cognitive factors, in shaping the Arabic as a first/heritage language and English as a second language of recently arrived Syrian refugee children in Canada (N = 133; mean age = 9 years old; mean family residency = 23 months). We found that Arabic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Similarly, Sorenson Duncan and Paradis (2020b) found that L2 input-output with older siblings positively influenced lexical and morphosyntactic skills in 5-year-old English L2 learners from diverse L1 backgrounds, but there was limited evidence that L2 input-output from mothers had an effect. Paradis et al (2020a) also found that more sibling interaction in English was associated with larger English-L2 vocabularies and morphological abilities among Arabic heritage-L1 children (see also Hamann et al 2020).…”
Section: Language Use At Homementioning
confidence: 94%
See 4 more Smart Citations
“…Similarly, Sorenson Duncan and Paradis (2020b) found that L2 input-output with older siblings positively influenced lexical and morphosyntactic skills in 5-year-old English L2 learners from diverse L1 backgrounds, but there was limited evidence that L2 input-output from mothers had an effect. Paradis et al (2020a) also found that more sibling interaction in English was associated with larger English-L2 vocabularies and morphological abilities among Arabic heritage-L1 children (see also Hamann et al 2020).…”
Section: Language Use At Homementioning
confidence: 94%
“…Pham and Tipton (2018) found that superior verbal short-term memory skills were associated with larger vocabularies in both the Vietnamese heritage-L1 and English-L2 of school age bilingual children in the United States (see also, Collins et al 2014 for Spanish-English bilinguals). Regarding studies with Arabic heritage-L1 bilinguals, Paradis et al (2020a) reported a robust relationship between non-verbal analytic reasoning abilities and Arabic-L1 and English-L2 vocabulary knowledge and morphological abilities in school age bilinguals. Similarly, Hamann et al (2020) found that differences in working memory abilities were predictive of differences in Arabic-L1 German-L2 children's performance on a sentence repetition task in both languages (but see Andreou et al 2020 who did not find evidence of a relationship).…”
Section: The Influence Of Cognitive Abilities On L2 and Heritage-l1 Developmentmentioning
confidence: 99%
See 3 more Smart Citations